2001
DOI: 10.1385/mb:19:2:125
|View full text |Cite
|
Sign up to set email alerts
|

Using 2', 7'-Dichlorodihydrofluorescein-diacetate to Assess Polysaccharides as Immunomodulating Agents

Abstract: Neutrophils play a key role in the defense against microbial infections. One of their primary weapons to destroy microbes is the production of reactive oxygen species (ROS). This paper shows how 2', 7'-dichlorodihydrofluorescein-diacetate (DCFH-DA) was used to measure the effects of polysaccharides on the production of ROS by polymorphonuclear leukocytes (PMNs). The DCFH-DA method has been designed to provide a highly sensitive, quantifiable, real-time assessment of ROS production by PMNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Neutrophils were separated from blood by the method of Bland et al [4]. Blood, obtained from the National Blood Service, was collected with informed consent from healthy screened individuals and transferred into sterile disposable universal bottles (Bibby Sterilin, now trading as Barloworld, Scientific, Stone, Staffs., U.K.) containing lipopolysaccharide‐free heparin [20 units/ml (Leo Laboratories, Dublin, Ireland)].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils were separated from blood by the method of Bland et al [4]. Blood, obtained from the National Blood Service, was collected with informed consent from healthy screened individuals and transferred into sterile disposable universal bottles (Bibby Sterilin, now trading as Barloworld, Scientific, Stone, Staffs., U.K.) containing lipopolysaccharide‐free heparin [20 units/ml (Leo Laboratories, Dublin, Ireland)].…”
Section: Methodsmentioning
confidence: 99%
“…A method for determining immunoregulation effects of oligosaccharide and polysaccharides has already been developed [4]. Various species of active oxygen produced from dioxygen, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…No maximum was set for any well. Further details on the 'DCFH-DA method' can be found in Bland et al 7 …”
Section: Dcfh-da Methodsmentioning
confidence: 99%
“…6 In most cases ROS production is desirable, however in the case of acute respiratory distress syndrome (ARDS), rheumatoid arthritis and ischemia-reperfusion injury the opposite is true. 7 Oligosaccharides such as laminari-oligosaccharides (b-(1 fi 3)-D D -glucans) have been shown to have a variety of effects on the immune system, such as inhibition of cancer metastasis, 8 antitumour activity, 9 immunological activity 10 and complement activation. 11 They are commonly found in higher fungi, plants and seaweeds.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report has shown that a range of carbohydrate elicitors have significant effect on the stimulation and inhibition of ROS in neutrophils. This observation was linked to the structure of the tested oligosaccharides [33].…”
Section: Introductionmentioning
confidence: 99%